2017
DOI: 10.1002/2017jd027061
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Stratospheric Reactive Nitrogen and Ozone Related to the QBO

Abstract: The stratospheric quasi‐biennial oscillation (QBO) dominates interannual variability of dynamical variables and trace constituents in the tropical stratosphere and provides a natural experiment to test circulation‐chemistry interactions. This work quantifies the relationships among ozone (O3), reactive nitrogen (NOy), and source gas N2O, and their links to the QBO, based on satellite constituent measurements and meteorological data spanning 2005–2014 (over four QBO cycles). Data include O3, HNO3, and N2O from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 73 publications
4
31
0
Order By: Relevance
“…The top panel of Figure shows that the QBO is clear in both data sets near 30 km in the tropics, with consistent phase and amplitude between the model and observations. This is consistent with previous results from Park et al (). Both WACCM and SAGE II‐OSIRIS also show similar variations outside of the tropics, as can be seen in the bottom two panels of Figure .…”
Section: Mergingsupporting
confidence: 94%
See 3 more Smart Citations
“…The top panel of Figure shows that the QBO is clear in both data sets near 30 km in the tropics, with consistent phase and amplitude between the model and observations. This is consistent with previous results from Park et al (). Both WACCM and SAGE II‐OSIRIS also show similar variations outside of the tropics, as can be seen in the bottom two panels of Figure .…”
Section: Mergingsupporting
confidence: 94%
“…We applied a standard linear regression model to the merged data in order to quantify NO x variability tied to the QBO, linear trends, and volcanic aerosol. The QBO coefficients (not shown) have similar structure and values to those derived by Park et al () using OSIRIS and WACCM NO x from 2005 to 2014, with good agreement between observational and model results. The novel information here regards the long‐term trends and volcanic aerosol fits in the regressions.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Detailed vertical and temporal structures of the QBO in O3 and NO2 were revealed through Stratospheric Aerosol and Gas Experiment (SAGE) II data by Zawodny and McCormick (1991), Hasebe (1994), and Chipperfield et al (1994), and through Global Ozone Monitoring by Occultation of Stars (GOMOS) data by Hauchecorne et al (2010) and Liu et al (2011). Also Park et al (2017) showed the detailed structures of the QBO in O3, NOx, N2O, and HNO3 by analyzing Optical Spectrograph and Infrared Imager System (OSIRIS) data. These studies demonstrated that, different from zonal-wind, temperature, and NO2, the ozone QBO has a distinctly sharp phase change (transition) at around 28km, where the transition occurs between dynamical control below and photochemical control above.…”
Section: Introductionmentioning
confidence: 99%